Ping pong. Vol. one - Matsumoto, Taiyo, 1967-; Arias, Michael (Viz signature., 2020)
"Ace high school table tennis players push their passion to the limit in this story of self-discovery, told by Eisner Award winner Taiyo Matsumoto. Makoto Smile Tsukimoto doesn't smile even though he's got a natural talent for playing ping pong. As one of the best players in school, all hopes are on him to win the regional high school tournament, but winning is not what Smile really wants to do. Will the fierce competition to be number one bring out his best or drive him away from the game?"--Provided by publisher.